The Influence of Integrity and Loyalty on the Performance of Bank Negara Indonesia Employees Mattoangin Main Branch Office Makassar City - Shafira Ramadhani H; Risma Niswaty; Muh Rizal S; A. Muhammad Rivai (Public Resource Innovation Management and Excellence, 2026)
Shafira Ramadhani H, 2023. The Effect of Integrity and Loyalty on the Performance of Bank Negara Indonesia Employees Mattoangin Main Branch Office Makassar City. Thesis. Business Administration Study Program. Faculty of Social Sciences and Law. Makassar State University. (Guided by Risma Niswaty and Muh. Rizal S.) This study aims to determine how the Influence of Integrity and Loyalty on Employee Performance Both Partially and Simultaneously where Bank Negara Indonesia Kantor Cabang Utama Mattoangin Makassar City is the object of his research. This research uses Quantitative research type. The data collection technique used is primary data (Questionnaire, Observation, and Documentation). The sample used was formulated using the Krejcie and Morgan tables as many as 170 respondents. Data is obtained from research results that are processed using data analysis. The results showed that the indicators used for each variable showed that Integrity and Loyalty had a significant effect on the Performance of Bank Negara Indonesia Employeesat the Mattoangin Main Branch in Makassar City. It is proven based on. This is proven based on the Correlation Test, t Test and F Test and the Coefficient of Determination Test on the data obtained.